Pengaruh Metode dan Media Pembelajaran Terhadap Prestasi Belajar Pendidikan Agama Islam Siswa SMP N 1 Tirtomoyo Wonogiri - Eni Hidayati; Khoiru Rohmad; Rizal Fathurrohman (PT. Nawa Edukasi Nusantara, 2025)
The weak learning process is a major issue in the current education system. Students feel bored in class as a result of the current learning procedure, which makes them very burdened with the content and assignments given by the teacher. Thus, for students to achieve good learning outcomes, learning strategies and the use of appropriate learning media are very important. This study aims to determine whether there is a significant effect of the use of methods and media on student achievement in Islamic religious education subjects. This study is a quantitative study with a causal type involving 48 grade VII students of SMP N 1 Tirtomoyo. Based on the results of data analysis, 7.832 was obtained as a fixed number with a significance level of 0.000 less than 0.05. This implies that there is an influence between learning methods and the use of learning media on student achievement or the combination of learning methods and the use of instructional media has a major effect on student achievement in PAI.